1976
DOI: 10.1093/jnci/57.4.865
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of JMV Marek's Disease Tumor: A Nonproductively Infected Transplantable Cell Lacking in Rescuable Virus2

Abstract: Cells of the JMV Marek's disease (MD) tumor, originally produced by rapid serial passage of MD lymphoma cells in chickens, were characterized to determine whether they were of host or donor origin and to ascertain certain virus-host cell interrelationships. Differences noted in blood group B surface alloantigens between tumor cells and host lymphocytes indicated a probable nonhost origin (i.e., transplantability) of the tumor. JMV spleen tumors contained predominantly large lymphoblasts bearing MD tumor-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…The JMV stock used for the experiments in this paper corresponded in its biological properties to the high-passage JMV(JMV-H) described by Spencer et al (1976), or JMV-S used by Stephens et al (1976). Accordingly, a great deal of their results could be confirmed by the results of this study.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The JMV stock used for the experiments in this paper corresponded in its biological properties to the high-passage JMV(JMV-H) described by Spencer et al (1976), or JMV-S used by Stephens et al (1976). Accordingly, a great deal of their results could be confirmed by the results of this study.…”
Section: Discussionmentioning
confidence: 60%
“…However, JMV at various passage levels also contained MDV as, for instance, demonstrated by characteristic bi-phasic mortality patterns of chickens inoculated with JMV tumour cells (Spencer etal, 191 A, 1976). Conclusive evidence against infectious virus being present in JMV materials was reported only by Stephens et al (1976). The same working group (Witter et al, 1975) detected on JMV lymphoblasts a surface antigen which was supposed to be identical with Marek's disease (MD) tumour-associated surface antigen (MATSA) demonstrated on MD lymphoblastoid cell lines (Powell et al, 1974;Witter et al, 1975).…”
Section: Introductionmentioning
confidence: 98%
“…Titres and other characteristics of these two vaccines are presented elsewhere in this paper. Virulent MD virus for challenge consisted of DEF infected with clone 102W of the JM strain (Stephens et al, 1976). Cell-associated stocks of HVT and MD virus were rapidly thawed and diluted immediately in cell culture medium.…”
Section: Virusesmentioning
confidence: 99%
“…The most compelling indication that HVT might stimulate anti-tumour immunity is the observation, first reported by Mason and Jensen (1971), that chickens vaccinated with HVT are resistant to the MD-derived transplantable tumour, JMV. These transplantable lymphoblasts bear MATSA (Witter etal, 1975), but do not express the virus-specific antigens that are detectable by serological techniques, and are lacking in rescuable virus (von Biilow and Weiland, 1977), although studies involving nucleic acid hybridisation have shown at least part of the MDV genome to be present in JMV cells (Stephens et al, 1976). We now report that immunisation with MDV-infected chicken kidney cells inactivated with glutaraldehyde protected against JMV transplants, and we suggest that cells abortively infected with MDV and lymphoblasts malignantly transformed by MDV have an antigen in common, although such an antigen has not been recognised serologically.…”
mentioning
confidence: 99%
“…JMV was originally dervied by Sevoian et al (1964) by serial passage in chickens of lymphoma cells induced by the JM isolate of MDV. The potency of JMV was attributed to the increased virulence of the virus, but investigations using sex chromosomes (Spencer et al, 1976) or B blood group alloantigens (Stephens et al, 1976) demonstrated the allograft nature of the tumour. The early passages of JMV probably carried MDV, as do the lymphoblastoid cell lines derived from MD lymphomas.…”
mentioning
confidence: 99%